An empirical analysis of zero-leverage and ultra-low leverage firms: Some UK evidence - Viet Dang (The University of Manchester, Manchester Business School, 2009)
This paper studies conservative debt policies, focusing on firms with no debt (zero-leverage) or with extremely low debt. Examining an unbalanced panel of U.K. firms, we show that debt conservatism is a common, persistent yet puzzling empirical regularity: nearly 10% of U.K. firms have zero leverage and 18% have market leverage of less than or equal to 1% (ultra-low leverage). Firms maintaining zero-leverage or ultra-low leverage are generally smaller, younger, and less profitable but have a higher payout ratio. These firms also have substantial cash reserves and rely heavily on equity financing in order to mitigate underinvestment incentives. Firms with high-growth opportunities are more likely to adopt and switch to an extremely conservative debt policy. Firms with a large deviation from the target leverage are more likely to lever up. Our explanations for the zero-leverage puzzle are inconsistent with the pecking order theory, inconclusive on the financial flexibility hypothesis but generally supportive of the underinvestment hypothesis and the dynamic trade-off theory.
Keywords: 330; capital structure; low-leverage; zero-leverage; underinvestment; financial flexibility